Nanotherapies Based on ROS Regulation in Oral Diseases - Xin Luo; Yanli Zhang; Yuting Zeng; Dehong Yang; Zhiyan Zhou; Ziting Zheng; Ping Xiao; Xian Ding; Qianlin Li; Jiaping Chen; Qianwen Deng; Xincen Zhong; et al. (Advanced Science, 2025)
Abstract Oral diseases rank among the most prevalent clinical conditions globally, typically involving detrimental factors such as infection, inflammation, and injury in their occurrence, development, and outcomes. The concentration of reactive oxygen species (ROS) within cells has been demonstrated as a pivotal player in modulating these intricate pathological processes, exerting significant roles in restoring oral functionality and maintaining tissue structural integrity. Due to their enzyme‐like catalytic properties, unique composition, and intelligent design, ROS‐based nanomaterials have garnered considerable attention in oral nanomedicine. Such nanomaterials have the capacity to influence the spatiotemporal dynamics of ROS within biological systems, guiding the evolution of intra‐ROS to facilitate therapeutic interventions. This paper reviews the latest advancements in the design, functional customization, and oral medical applications of ROS‐based nanomaterials. Through the analysis of the components and designs of various novel nanozymes and ROS‐based nanoplatforms responsive to different stimuli dimensions, it elaborates on their impacts on the dynamic behavior of intra‐ROS and their potential regulatory mechanisms within the body. Furthermore, it discusses the prospects and strategies of nanotherapies based on ROS scavenging and generation in oral diseases, offering alternative insights for the design and development of nanomaterials for treating ROS‐related conditions.